Acute prolonged motor aura resembling ischemic stroke after COVID – 19 vaccination (CoronaVac): the first case report (P1-1.Virtual) - Wanakorn Rattanawong; Wasan Akaratanawat; Supatporn Tepmongkol; Aurauma Chutinet; Nijasri Charnnarong (Neurology, 2022)
NA
Keywords: Acute Ischemic Stroke Management; Retinal and Optic Conditions; Intramuscular injections and effects